Applications of remote sensing in the monitoring of rice crops - Tan, Chue Poh; Koay, Jun Yi; Lim, Ka Sing; Saiful Bahari, Abu Bakar; Ewe, Hong Tat, Dr.; Chuah, Hean Teik, Dato' Prof. Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/